High-strength wear-resistant fluorocarbon wire and preparation method thereof
Patent Information
- Application Number
- CN202611281064.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-24
AI Technical Summary
在聚合物基体改性方面,通过与六含氟单体共聚以改善线材柔韧性,但是强度降低,因此在树脂中添加碳纳米管、石墨烯或层状硅酸盐等无机填料以增强
1、通过在偏氟乙烯共聚物中引入含氟丙烯酸酯单元,配合聚醚二胺、相转移催化剂、润滑减摩纳米颗粒及无机层状填料进行反应共混挤出造粒,再经熔融纺丝、水槽淬火固化及三级梯度拉伸热定型工艺,制得氟碳线。克服氟树脂与无机填料相容性差、易发生相分离的问题。
Smart Images

Figure CN122791497B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fluorocarbon wire technology, specifically to a high-strength, wear-resistant fluorocarbon wire and its preparation method. Background Technology
[0002] Fluorocarbon steel lines possess excellent weather resistance, corrosion resistance, and high-density sinking properties, playing a vital role in high-end fishing lines, specialty marine cables, and outdoor sewing threads. However, as the requirements for the mechanical strength and abrasion resistance of steel lines gradually increase, traditional fluorocarbon steel lines are prone to surface wear, fraying, and even breakage, failing to meet the high durability demands of harsh environments.
[0003] To improve the overall performance of fluorocarbon wires, existing research mainly focuses on raw material modification and physical blending. Regarding polymer matrix modification, copolymerization with hexafluorinated monomers improves wire flexibility, but reduces strength. Therefore, inorganic fillers such as carbon nanotubes, graphene, or layered silicates are added to the resin for reinforcement. However, copolymerization of fluorinated monomers alone leads to a decrease in matrix crystallinity, sacrificing tensile strength while improving flexibility. Direct physical blending of inorganic nanofillers, due to the low surface energy of vinylidene fluoride resin, causes filler agglomeration during melt extrusion, which reduces tensile strength and surface abrasion resistance, leading to interfacial delamination after prolonged use. Mechanical properties and abrasion resistance cannot be simultaneously achieved. Therefore, this paper proposes a high-strength, abrasion-resistant fluorocarbon wire and its preparation method. Summary of the Invention
[0004] The purpose of this invention is to provide a high-strength, wear-resistant fluorocarbon yarn and its preparation method. Overcoming the shortcomings of existing technologies where it is difficult to simultaneously achieve both wear resistance and strength in fluorocarbon monofilaments, this invention provides a method for preparing a high-strength, wear-resistant fluorocarbon yarn.
[0005] The specific technical solution is as follows: A method for preparing a high-strength, wear-resistant fluorocarbon wire, the preparation method is as follows: Step (1) Aqueous suspension copolymerization of vinylidene fluoride active precursor resin: Deionized water and a suspending agent were added to the reactor. The reactor was then evacuated and purged with high-purity nitrogen (≥99.99%) at least three times to remove oxygen from the reaction system. Fluorinated acrylate monomers, vinylidene fluoride monomers, and a chain transfer agent were then introduced. Stirring was started, and the temperature was raised to 35℃-55℃. A deionized aqueous solution containing an initiator was then introduced to initiate the polymerization reaction. During polymerization, the pressure inside the reactor was maintained between 3.0MPa and 4.0MPa by continuously adding vinylidene fluoride monomers. After reacting for 3.5-6.0 hours, the reactor was cooled and the unreacted monomers were released. The reaction product was centrifuged, filtered, washed 3-5 times with deionized water, and washed 2-3 times with anhydrous ethanol. It was then vacuum-dried at 65℃-85℃ for 10-16 hours to obtain a vinylidene fluoride copolymer precursor powder with active ester side groups. The reactor is equipped with a double-layer turbine stirrer with a stirring speed of 220 rpm–250 rpm, and is equipped with a temperature-pressure safety interlock system. After the reaction, residual VDF monomer is removed to a safe concentration by overpressure relief and nitrogen purging. Furthermore, in the copolymer precursor, the molar content of fluorinated acrylate structural units is 1.0 mol%–5.0 mol%, providing sufficient crosslinking sites for subsequent melt ammonolysis.
[0006] Preferably, by mass, the proportions and process conditions of the reactants in step (1) are as follows: 5000-8000 parts deionized water, 1.5-4.0 parts suspending agent, 8.0-15.0 parts fluorinated acrylate monomer, 450-550 parts vinylidene fluoride monomer, 0.8-2.0 parts chain transfer agent, and 0.4-1.0 parts initiator; the reaction temperature is 40℃-55℃, the pressure inside the reactor is 3.1MPa-3.8MPa, the reaction time is 4.0h-5.5h, the vacuum drying temperature is 70℃-80℃, and the drying time is 11h-15h.
[0007] Preferably, the reactant ratio and process conditions in step (1) are as follows: 6500-7000 parts deionized water, 2.2-2.8 parts suspending agent, 10.0-11.5 parts fluorinated acrylate monomer, 485-500 parts vinylidene fluoride monomer, 1.1-1.4 parts chain transfer agent, and 0.55-0.70 parts initiator; the reaction temperature is 44℃-46℃, the pressure inside the reactor is 3.3MPa-3.5MPa, the reaction time is 4.8h-5.0h, the vacuum drying temperature is 74℃-76℃, and the drying time is 12h-13h.
[0008] Preferably, the suspending agent is one of hydroxypropyl methylcellulose, methylcellulose, polyvinyl alcohol, and gelatin, with hydroxypropyl methylcellulose being the most preferred.
[0009] Preferably, the fluorinated acrylate monomer is one of 2,2,2-trifluoroethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, perfluorooctyl ethyl methacrylate, and 2,2,2-trifluoroethyl methacrylate, and more preferably 2,2,2-trifluoroethyl methacrylate.
[0010] Preferably, the chain transfer agent is one of acetone, ethyl acetate, diethyl carbonate, and isopropanol, with acetone being the most preferred.
[0011] Preferably, the initiator is one of diisopropyl peroxide dicarbonate, di(2-ethylhexyl) peroxide dicarbonate, or tert-butyl peroxide isobutyrate, with diisopropyl peroxide dicarbonate being the most preferred.
[0012] Step (1) During suspension copolymerization, ensure that the residual oxygen content in the reactor is below 10 ppm. Disperse the fluorinated acrylate monomer and vinylidene fluoride monomer in the aqueous phase using a suspending agent to form stable microdroplets. The free radicals generated by the initiator decomposition initiate copolymerization. A constant-pressure automatic feeding system with a feed pump and pressure sensor is used to replenish the vinylidene fluoride monomer. The pressure fluctuation range is limited to ±0.1 MPa by controlling the feed pump to ensure the uniformity of the copolymer's side group composition. During the reaction, as the monomer is consumed, VDF is replenished at constant pressure using the feed pump, with a cumulative replenishment amount of 580-600 kg per batch. After the reaction, a closed-loop recovery system is used. Unreacted residual gaseous monomers are recovered (direct venting is strictly prohibited, and explosion venting and interlocking safety requirements must be met), and the total monomer conversion rate is controlled at 88%-92%. During product washing, deionized water is first used to wash away residual suspending agents, and then anhydrous ethanol is used to wash away unreacted fluorinated acrylate oligomers. The Mw value of the obtained precursor powder is controlled at 450,000-600,000. Nuclear magnetic resonance spectroscopy is used with deuterated acetone as solvent to calculate the mole fraction of fluorinated acrylates by integration. The monomer conversion rate is obtained by material balance calculation based on the ratio of the initial total feed amount to the final dried precursor weight.
[0013] Step (2) Melt reaction blending and in-situ exfoliation granulation of inorganic materials: By weight, take 1000 parts of the vinylidene fluoride copolymer precursor powder obtained in step (1), add 0.8 to 12.0 parts of polyether diamine, 0.01 to 0.1 parts of phase transfer catalyst, 1.0 to 8.0 parts of lubricating and friction-reducing nanoparticles, and 1.0 to 10.0 parts of inorganic layered filler; dry mix and premix in a high-speed mixer at a speed of 500 rpm to 1500 rpm for 1.5 min to 5 min, and then add the mixture to a material with an aspect ratio of 36: In a co-rotating parallel twin-screw extruder with a ratio of 1 to 48:1, the temperatures of each zone of the extruder are set as follows: feeding zone 1 140℃ to 175℃, reaction zone 2 170℃ to 205℃, reaction zone 3 180℃ to 200℃, homogenization zone 4 190℃ to 215℃, and die head 185℃ to 210℃. The screw speed is 100 rpm to 200 rpm. The extruded material is water-cooled, stretched, air-dried, and pelletized. It is then dried in an oven at 70℃ to 90℃ for 2 to 6 hours to obtain modified fluorocarbon pellets.
[0014] Preferably, by mass, the reactant ratio and process conditions in step (2) are as follows: 1000 parts of vinylidene fluoride copolymer precursor powder, 3.0 to 9.0 parts of polyether diamine, 0.03 to 0.1 parts of phase transfer catalyst, 2.0 to 5.0 parts of lubricating and friction-reducing nanoparticles, and 3.0 to 7.0 parts of inorganic layered filler; the high-speed dry mixing speed is 800 rpm to 1200 rpm, and the mixing time is 2 min to 4 min; the temperature settings of each zone of the twin-screw extruder are as follows: feeding zone 1 150℃ to 168℃, reaction zone 2 180℃ to 200℃, reaction zone 3 185℃ to 198℃, homogenization zone 4 198℃ to 208℃, and die head 192℃ to 203℃; the screw speed is 120 rpm to 170 rpm; the oven drying temperature is 75℃ to 85℃, and the drying time is 3.0 h to 5.0 h.
[0015] Preferably, the reactant ratio and process conditions in step (2) are as follows: 1000 parts of vinylidene fluoride copolymer precursor powder, 4.5 to 7.5 parts of polyether diamine, 0.03 to 0.08 parts of phase transfer catalyst, 2.5 to 4.0 parts of lubricating and friction-reducing nanoparticles, and 4.0 to 6.0 parts of inorganic layered filler; the high-speed dry mixing speed is 950 rpm to 1050 rpm, and the mixing time is 2.8 min to 3.2 min.
[0016] The temperature settings for each zone of the twin-screw extruder are as follows: feeding zone 1 158℃ to 163℃, reaction zone 2 188℃ to 193℃, reaction zone 3 185℃ to 195℃, homogenization zone 4 203℃ to 207℃, and die head 198℃ to 202℃; the screw speed is 145 rpm to 155 rpm; the oven drying temperature is 78℃ to 82℃, and the drying time is 3.5h to 4.5h.
[0017] Preferably, the reactant ratio and process conditions in step (2) are as follows: 1000 parts of vinylidene fluoride copolymer precursor powder, 5.5 to 6.5 parts of polyether diamine, 0.035 to 0.040 parts of phase transfer catalyst, 2.8 to 3.2 parts of lubricating and friction-reducing nanoparticles, and 4.8 to 5.2 parts of inorganic layered filler; the high-speed dry mixing speed is 1000 rpm, and the mixing time is 3 min; the temperature settings of each zone of the twin-screw extruder are as follows: feeding zone 1 160℃, reaction zone 2 190℃, reaction zone 3 195℃, homogenization zone 4 205℃, and die head 200℃; the screw speed is 150 rpm; the oven drying temperature is 80℃, and the drying time is 4.0 h.
[0018] Preferably, the polyether diamine is one of polypropylene glycol bis-2-aminopropyl ether D2000, polypropylene glycol bis-2-aminopropyl ether D400, and ED2003, a polymer of methyl ethylene oxide and ethylene oxide and bis(2-aminopropyl) ether, and more preferably polypropylene glycol bis-2-aminopropyl ether D2000.
[0019] Preferably, the phase transfer catalyst is one of benzyltriphenylphosphine chloride, tetrabutylphosphine bromide, tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate, and trioctylmethylammonium chloride, with benzyltriphenylphosphine chloride being the most preferred.
[0020] Preferably, the lubricating and friction-reducing nanoparticles are one of hexagonal boron nitride nanosheets, molybdenum disulfide nanosheets, tungsten disulfide nanosheets, and graphene nanosheets, with hexagonal boron nitride nanosheets being the most preferred.
[0021] Preferably, the inorganic layered filler is one of octadecyltrimethylammonium chloride modified montmorillonite, quaternary ammonium salt modified hydrotalcite, and organic modified kaolinite, with octadecyltrimethylammonium chloride modified montmorillonite being the most preferred.
[0022] The octadecyltrimethylammonium chloride-modified montmorillonite can be prepared by methods including but not limited to the following: 2500 parts of deionized water are injected, 100 parts of sodium-based montmorillonite are added under stirring at 350 rpm, steam is introduced to raise the temperature to 70°C, and this temperature is maintained for high-shear dispersion for 2 hours to allow the montmorillonite to fully swell and peel off; 200 parts of deionized water and 200 parts of industrial ethanol are added to a mixing tank, along with 38.2 parts of octadecyltrimethylammonium chloride, and the mixture is heated to 60°C and stirred to dissolve, obtaining a modifier solution. This solution is then pumped into a montmorillonite reactor within 30 minutes using a metering pump, and the temperature is raised to 82°C and maintained for 3.5 hours; after the reaction, the mixture is sent to a plate and frame filter press for filtration, and washed with 60°C hot water until the conductivity of the effluent is less than 50 μS / cm; the filter cake is sent to a flash dryer and dried at 180°C until the moisture content is less than 0.5%, and after air jet milling, organic montmorillonite products with a D50 less than or equal to 2.0 μm are collected.
[0023] The quaternary ammonium salt modified hydrotalcite can be obtained by methods including but not limited to the following: 600 parts of deionized water are injected into a first mixing tank, along with 153.8 parts of magnesium nitrate and 75.0 parts of aluminum nitrate, and stirred to dissolve and form a salt solution; 600 parts of deionized water are injected into a second mixing tank, along with 64.0 parts of sodium hydroxide, 10.6 parts of sodium carbonate, and 29.1 parts of hexadecyltrimethylammonium bromide, and the mixture is heated to 50°C and stirred to dissolve and form an alkaline solution; 200 parts of water are added to the bottom of a co-precipitation vessel, and the mixture is heated under nitrogen to [temperature missing]. At 60℃, the stirring speed is turned on at 400rpm; a dual-channel metering pump simultaneously pumps in the salt solution and alkali solution, and the feed flow rate is automatically adjusted to strictly control the pH value in the reactor at 10.0. After the feeding is completed within 1.5 hours, the temperature is raised to 105℃, and hydrothermal crystallization is carried out for 10 hours; the suspension is dehydrated by a horizontal screw centrifuge, washed with 50℃ hot water until the pH of the filtrate is close to 7.0; water is added and the mixture is slurried until the solid content is 15%, and then sent to a centrifugal spray drying tower with an inlet air temperature of 220℃ and an outlet air temperature of 90℃ to obtain spherical modified hydrotalcite powder.
[0024] Organically modified kaolin can be obtained by methods including but not limited to the following: 900 parts of dimethyl sulfoxide and 100 parts of deionized water are added, along with 100 parts of calcined kaolin. After sealing the reactor, the temperature is raised to 65°C, and the mixture is continuously stirred and intercalated for 36 hours. After pressure filtration, the filtrate is sent to a recovery tower for distillation and recovery. The wet cake falls into a coupling vessel, and 800 parts of a 95% ethanol aqueous solution are added and dispersed into a homogeneous suspension. Glacial acetic acid is added to adjust the pH to 4.8, and 5.0 parts of a silane coupling agent KH-550 and 3.0 parts of an ethanol solution of octadecylamine are added. The mixture is heated to 78°C and refluxed for 5 hours. The slurry is sent to a vacuum disc dryer and dried at 85°C and a vacuum of -0.09 MPa for 12 hours while recovering ethanol. The dried material is then pulverized by a fully enclosed nitrogen-protected airflow pulverizer to collect organically modified kaolin products with a mesh size of 325 or larger. In step (2), during the twin-screw extrusion process, the high temperature and high shear field in reaction zone 2 and reaction zone 3 cause the primary amino group at the end of the polyether diamine to undergo nucleophilic ammonolysis with the ester group of the copolymer side group, releasing trifluoroethanol gas and forming flexible nodes connected by amide groups. In the vacuum degassing section of the extruder, by maintaining the vacuum degree at -0.08MPa to -0.095MPa, the byproduct trifluoroethanol gas and trace amounts of moisture in the system generated by the ammonolysis reaction can be reliably extracted, thus avoiding the generation of porosity defects inside the pellets from the source.
[0025] Step (3) Monofilament melt spinning extrusion The modified fluorocarbon pellets prepared in step (2) were placed in a single-screw spinning machine for melt spinning. The length-to-diameter ratio of the screw used was in the range of 28:1-36:1. The controlled temperatures of each spinning section were as follows: melting zone 180℃-215℃, extrusion zone 200℃-235℃, and spinneret 195℃-230℃. After the melt passed through a single-hole or multi-hole spinneret with an aperture between 0.5mm and 1.2mm, it formed nascent filaments, which were immediately introduced into a water bath with a water temperature of 30℃-65℃ for quenching and solidification. The traction speed was adjusted to 10m / min-22m / min.
[0026] Preferably, in step (3), the screw length-to-diameter ratio of the single-screw spinning machine is selected as 30:1-34:1; the spinning temperature is 190℃-210℃ in the melting zone, 210℃-230℃ in the extrusion zone, and 205℃-225℃ in the spinneret; the spinneret orifice diameter is set to 0.7mm-0.9mm; the water temperature of the quenching water tank is controlled at 40℃-60℃; and the traction line speed is maintained at 12m / min-18m / min.
[0027] In step (3), the modified pellets must be dried before feeding to reduce the moisture content to below 200 ppm. In addition, the vertical distance between the spinneret orifice and the surface of the quenching water tank must be strictly maintained within the range of 30 mm to 80 mm.
[0028] Step (4) Three-stage gradient thermal stretching and surface phase separation shaping, including a first-stage stretching stage, a second-stage stretching stage, and a third-stage thermal shaping and surface self-lubrication stage, specifically: The nascent filaments are continuously fed into a hot air oven or hot water bath at 110℃-140℃ to complete uniaxial stretching of 3.5 to 5.2 times. The filaments that have undergone primary stretching are then introduced into an oven at 140℃-170℃ to apply micro-stretching of 1.2 to 2.2 times, so that the cumulative total stretching ratio reaches 6.0 to 9.5 times. The resulting filaments are then fed into a heat-setting oven at 155℃-180℃ and heat-set for 4 to 10 seconds at an overfeed shrinkage rate of 1% to 6%. After being dried by a cooling fan, the filaments are wound to obtain high-strength, wear-resistant fluorocarbon wire with a diameter between 0.15 mm and 0.40 mm.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Fluorocarbon yarns are produced by introducing fluorinated acrylate units into vinylidene fluoride copolymers, combined with polyether diamine, phase transfer catalysts, lubricating and friction-reducing nanoparticles, and inorganic layered fillers through reactive blending, extrusion granulation, followed by melt spinning, water bath quenching and curing, and three-stage gradient stretching heat setting processes. This overcomes the problems of poor compatibility between fluoropolymers and inorganic fillers and the tendency for phase separation.
[0030] 2. Through the reaction of polyether diamine molecular chains with fluorinated ester groups of copolymer side chains, flexible amide crosslinking nodes are constructed in situ inside the matrix. At the same time, the phase transfer catalyst assists the inorganic layered filler in overcoming the interlayer van der Waals forces, the interlayer spacing is greatly expanded and effective exfoliation is achieved. The exfoliated nanosheets and lubricating and friction-reducing nanoparticles are interwoven and crosslinked in the matrix, inhibiting the tendency of inorganic particles to aggregate in the melt and achieving a homogeneous distribution of the nanophase in the matrix.
[0031] 3. The exfoliated nanofillers and cross-linked networks enable smooth stress transmission and balanced dispersion when the material is subjected to force, giving the wire high rigidity and high toughness. In addition, the exfoliated nanosheets are easy to migrate and spread into a self-lubricating transfer film on the material surface under frictional shear force, which reduces the friction coefficient of the material in steady-state friction process and does not produce stick-slip oscillation, thus enhancing the wear resistance and fatigue life of the wire under dynamic reciprocating friction conditions.
[0032] 4. By combining melt spinning with water bath quenching and solidification and three-stage gradient stretching heat setting process, the polymer macromolecular chains and nanofillers are guided to form a highly crystalline structure along the axis, eliminating residual stress and micro-defects inside the wire; the entire reaction blending and spinning process is highly controllable and efficient, meeting the requirements for large-scale continuous industrial manufacturing of high-performance fluorocarbon wires. Attached Figure Description
[0033] Figure 1 The X-ray diffraction (XRD) patterns of the composite materials obtained from the montmorillonite raw material, Example 1, and Comparative Example 3 of this invention are shown. Figure 2 The original stress-strain tensile property test curves of the composite materials obtained in Example 1, Comparative Example 1, and Comparative Example 4 of this invention are shown. Figure 3 The graphs show the dynamic friction coefficient-test stroke curves of the composite materials obtained in Example 1, Comparative Example 1, and Comparative Example 4 of this invention during reciprocating friction testing. Detailed Implementation
[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] Please see Figures 1 to 3 This invention provides a high-strength, wear-resistant fluorocarbon wire and its preparation method, the technical solution of which is as follows: The specific material information involved in this plan is as follows: Vinylidene fluoride purity ≥ 99.9%, specifically a product of Hangzhou Yile Rubber & Plastics Co., Ltd., with a melt index (230℃, 2.16kg) of 3 and a weight-average molecular weight Mw = 5.6 × 10⁻⁶. 5 g / mol; 2,2,2-trifluoroethyl methacrylate, purity ≥99.0%, purchased from Beijing Innocare Technology Co., Ltd., CAS 352-87-4; 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, purity ≥99.0%, CAS 3063-94-3; perfluorooctyl ethyl methacrylate, purity ≥98.0%, CAS 1996-88-9; 2,2,2-trifluoroethyl methacrylate, purity ≥98.5%, CAS 407-47-6; hydroxypropyl methylcellulose, viscosity 400 mPa·s, CAS 9004-65-3, purchased from Merck Chemicals; polyvinyl alcohol, degree of alcoholysis 88%, type PVA17-88; diisopropyl peroxide, industrial grade, CAS 105-64-6, purchased from Aladdin Reagent Co., Ltd.; di(2-ethylhexyl) peroxide, CAS 105-64-6; di(2-ethylhexyl) peroxide, CAS 105-64-6, purchased from Aladdin Reagent Co., Ltd. The average molecular weight of 16111-62-9 is tert-butyl peroxide (2-aminopropyl peroxide), CAS number 109-13-7; the average molecular weight of polypropylene glycol bis(2-aminopropyl) ether D2000 is 2000, CAS number 9046-10-0; the average molecular weight of polypropylene glycol bis(2-aminopropyl) ether D400 is 400, CAS number 9046-10-0; the average molecular weight of ED2003, a polymer of methyl ethylene oxide and ethylene oxide and bis(2-aminopropyl) ether, is 400. The molecular weight is 2000, and the CAS number is 65605-36-9; benzyltriphenylphosphine chloride has a purity of ≥99.0%, and the CAS number is 1100-88-5, purchased from Sigma; tetrabutylphosphine bromide has the CAS number 3115-68-2; tetrabutylammonium bromide has the CAS number 1643-19-2, purchased from Aladdin; tetrabutylammonium hydrogen sulfate has the CAS number 32503-27-8; and trioctylmethylammonium chloride has the CAS number 5137-55-3. Hexagonal boron nitride nanosheets with a purity ≥99.3% and a sheet diameter ≤1.5μm; nano-molybdenum disulfide with a purity ≥99.0% and an average particle size of 50nm; nano-tungsten disulfide with a purity ≥99.0% and an average particle size of 50nm; graphene nanosheets with a purity ≥98.0% and a particle size of 1-5nm; 1000kg of high-purity sodium-based montmorillonite with a cation exchange capacity of 95mmol / 100g, model: NanolinDK1; industrial-grade magnesium nitrate hexahydrate and industrial-grade aluminum nitrate nonahydrate with a purity ≥98%; ultrafine calcined kaolin 4000 mesh, model: Ultrafine-4000; high-purity nitrogen with a purity ≥99.99%.
[0036] Example 1 First, aqueous suspension copolymerization of the vinylidene fluoride active precursor resin was performed. 6750L of deionized water and 2.5kg of hydroxypropyl methylcellulose were added to the reactor. The reactor was then evacuated and purged four times with high-purity nitrogen (≥99.99%) until the oxygen content inside the reactor was reduced to less than 10ppm. Then, 10.8kg of [unspecified substance] was injected. 2,2,2-Trifluoroethyl methacrylate monomer, 492 kg of vinylidene fluoride monomer, and 1.25 kg of acetone chain transfer agent were used. The stirring speed was turned on at 220 rpm, and the temperature was raised to 45°C. Deionized water containing 0.625 kg of diisopropyl peroxide initiator was injected to start polymerization. During the reaction, vinylidene fluoride monomer was automatically added through an automatic feeding system controlled by a feed pump and a pressure sensor to maintain the pressure inside the reactor between 3.35 MPa and 3.45 MPa. After reacting for 4.9 h, the reactor was cooled and vented. The product was centrifuged and filtered, washed 4 times with deionized water and 2 times with anhydrous ethanol, and vacuum dried at 75°C for 12.5 h to obtain a vinylidene fluoride copolymer precursor powder containing active ester side groups and a weight average molecular weight of 520,000.
[0037] Next, melt reaction blending and in-situ exfoliation granulation of inorganic materials were carried out; 1000 kg of the obtained vinylidene fluoride copolymer precursor powder was analyzed by 1H-NMR. The active ester side group content was tested to be 2.2 mol%. 6.0 kg of polypropylene glycol bis-2-aminopropyl ether D2000, 0.030 kg of benzyltriphenylphosphine chloride phase transfer catalyst, 3.0 kg of hexagonal boron nitride nanosheets, and 5.0 kg of octadecyltrimethylammonium chloride modified montmorillonite were added and dry-mixed at 1000 rpm for 3 min in a high-speed mixer. The mixture was then fed into a co-rotating parallel twin-screw extruder with a length-to-diameter ratio of 40:1. The extrusion temperatures were set as follows: feeding zone 1 160℃, reaction zone 2 190℃, reaction zone 3 190℃, homogenization zone 4 205℃, and die head 200℃; the screw speed was 150 rpm; the vacuum degree in the vacuum degassing section was maintained at -0.09 MPa. The extruded material was water-cooled, stretched, and air-dried into pellets, then dried in an 80℃ oven for 4.0 h to obtain modified fluorocarbon pellets. X-ray diffraction tests showed that the interlayer spacing of modified montmorillonite in the resin was 36% larger than that of the raw modified montmorillonite.
[0038] Then, monofilament melt spinning and extrusion are performed. The modified fluorocarbon pellets with a moisture content of less than 150 ppm are fed into a single-screw spinning machine with an aspect ratio of 32:1. The spinning heating temperature is set as follows: 200°C in the melting zone, 220°C in the extrusion zone, and 215°C at the spinneret. The melt is extruded through a spinneret with a diameter of 0.8 mm and quenched and solidified in a water bath at 50°C. The spinneret is 40 mm above the water surface, and the traction linear speed is 15 m / min, resulting in nascent fine filaments.
[0039] Finally, a three-stage gradient hot stretching and surface phase separation and shaping process is performed. The nascent filaments undergo the following steps in sequence: first, 4.5 times uniaxial stretching is performed in a 125℃ hot air oven; second, 1.8 times micro-stretching is performed in a 155℃ oven, so that the cumulative total stretching ratio reaches 8.1 times; third, heat setting is performed in a 165℃ heat setting oven with a 3% overfeed shrinkage rate for 6 seconds, and after drying, they are wound to obtain a high-strength wear-resistant fluorocarbon wire with a diameter of 0.25mm.
[0040] Example 2 First, aqueous suspension copolymerization of the active precursor resin of vinylidene fluoride was carried out. 6600L of deionized water and 2.6kg of hydroxypropyl methylcellulose were added to the reactor, and the reactor was evacuated and purged with high-purity nitrogen to control the oxygen content in the reactor to be below 10ppm. 11.0kg of 2,2,2-trifluoroethyl methacrylate monomer, 490kg of vinylidene fluoride monomer and 1.3kg of acetone were injected. After heating to 46℃, a deionized aqueous solution containing 0.60kg of diisopropyl peroxide was injected to start the polymerization. During the reaction, the reactor pressure was maintained between 3.25MPa and 3.35MPa by linking the feed pump and the pressure sensor. The reaction time was 4.8h. After washing, the product was vacuum dried at 76℃ for 12h to obtain a precursor powder of vinylidene fluoride copolymer containing active ester side groups.
[0041] Next, melt reaction blending and in-situ exfoliation granulation of inorganic materials were carried out. 1000 kg of the precursor powder was taken, and 5.0 kg of polypropylene glycol bis-2-aminopropyl ether D2000, 0.035 kg of tetrabutylammonium bromide phase transfer catalyst, 3.5 kg of hexagonal boron nitride nanosheets, and 4.5 kg of octadecyltrimethylammonium chloride modified montmorillonite were added. The mixture was dry-mixed in a high-speed mixer at 1000 rpm for 3 min. The mixture was then fed into a twin-screw extruder with a length-to-diameter ratio of 40:1. The extrusion temperature was set as follows: zone 1 162℃, zone 2 192℃, zone 3 195℃, zone 4 206℃, and die head 201℃; the screw speed was 155 rpm; and the vacuum degree of the vacuum degassing section was -0.088 MPa. After pelleting, the pellets were dried at 80℃ for 4.0 h to obtain modified fluorocarbon pellets.
[0042] Then, monofilament melt spinning and extrusion are carried out; the pellets are fed into a single screw spinning machine with an aspect ratio of 32:1, and the spinning temperature is set as follows: 198℃ in the melting zone, 218℃ in the extrusion zone, and 213℃ in the spinneret; the spinneret orifice diameter is 0.8mm, the quenching water temperature is 48℃, and the traction linear speed is 15m / min, and the filaments are extruded into nascent fine filaments.
[0043] Finally, a three-stage gradient hot stretching and surface phase separation and setting process is performed; the nascent filaments are stretched 4.4 times at the first-stage stretching temperature of 124℃, and then slightly stretched 1.8 times at the second-stage stretching temperature of 154℃, with a total stretching ratio of 7.92 times; then they are placed in an oven at the third-stage heat setting temperature of 164℃ and heat-set for 6 seconds with a 3% overfeed shrinkage rate, and finally dried and wound to obtain a high-strength wear-resistant fluorocarbon wire with a diameter of 0.25mm.
[0044] Example 3 First, aqueous suspension copolymerization of the vinylidene fluoride active precursor resin was carried out. 6500 L of deionized water and 3.0 kg of methylcellulose were added to the reactor, and the reactor was evacuated and purged with high-purity nitrogen. 12.0 kg of 1,1,1,3,3,3-hexafluoroisopropyl methacrylate monomer, 510 kg of vinylidene fluoride monomer, and 1.4 kg of ethyl acetate were then introduced. The temperature was raised to 48 °C, and a deionized aqueous solution containing 0.70 kg of di(2-ethylhexyl) peroxide dicarbonate was introduced to initiate polymerization. During the reaction, the reactor pressure was maintained between 3.42 MPa and 3.58 MPa by a feed pump linked to a pressure sensor, and the reaction time was 4.5 h. After washing, the product was vacuum dried at 75 °C for 13 h to obtain the copolymer precursor powder.
[0045] Next, melt reaction blending and in-situ exfoliation granulation of inorganic materials were carried out. 1000 kg of the precursor powder was taken, and 7.5 kg of methyl ethylene oxide and ethylene oxide and bis(2-aminopropyl) ether polymer ED2003, 0.045 kg of tetrabutylphosphine bromide, 4.0 kg of nano molybdenum disulfide and 6.0 kg of quaternary ammonium salt modified hydrotalcite were added. The dry mixing speed was 1100 rpm and the time was 2.5 min. The twin-screw extrusion temperature was set as follows: zone 1 165℃, zone 2 195℃, zone 3 200℃, zone 4 208℃, and die head 202℃. The screw speed was 160 rpm. The vacuum degree in the vacuum degassing section was maintained at -0.085 MPa. After pelleting, the pellets were dried in an oven at 82℃ for 3.5 h to obtain modified fluorocarbon pellets.
[0046] Then, monofilament melt spinning and extrusion are carried out. The pellets are fed into a single screw spinning machine with a length-to-diameter ratio of 34:1. The spinning temperature is set as follows: melting zone 205℃, extrusion zone 225℃, spinneret 220℃; spinneret orifice diameter is 0.75mm, quenching water bath temperature is 52℃, and traction linear speed is 16m / min to obtain nascent fine filaments.
[0047] Three-stage gradient hot stretching and surface phase separation and setting were carried out; the nascent filaments were stretched 4.6 times at the first-stage stretching temperature of 128℃ and 1.7 times at the second-stage stretching temperature of 158℃, with a cumulative total stretching ratio of 7.82 times; the third-stage heat setting temperature was 168℃, and heat setting was carried out for 5 seconds with an overfeed shrinkage rate of 2.5%, finally producing a high-strength wear-resistant fluorocarbon wire with a diameter of 0.23mm.
[0048] Example 4 First, aqueous suspension copolymerization of the vinylidene fluoride active precursor resin was carried out. 5500L of deionized water and 3.5kg of polyvinyl alcohol were added to the reactor. The reactor was evacuated and the air was replaced with high-purity nitrogen. 14.0kg of perfluorooctyl ethyl methacrylate monomer, 530kg of vinylidene fluoride monomer and 1.8kg of diethyl carbonate were then added. The temperature was raised to 52℃, and a deionized aqueous solution containing 0.85kg of tert-butyl isobutyrate peroxide was added to start the polymerization. During the reaction, the reactor pressure was maintained between 3.60MPa and 3.80MPa by linking the feed pump with the pressure sensor. The reaction time was 4.0h. After washing, the product was vacuum dried at 80℃ for 11h to obtain the precursor powder.
[0049] The process involves melt reaction blending and in-situ exfoliation granulation of inorganic materials. Specifically, 1000 kg of the precursor powder is mixed with 10.0 kg of polypropylene glycol bis-2-aminopropyl ether D400, 0.080 kg of benzyltriphenylphosphine chloride, 6.0 kg of graphene nanosheets, and 8.0 kg of organically modified kaolin. The mixture is then dry-mixed at 1200 rpm for 2 min. The twin-screw extrusion temperatures are set as follows: zone 1: 170℃, zone 2: 195℃, zone 3: 200℃, zone 4: 210℃, and die head: 205℃. The screw speed is 180 rpm. The vacuum level in the vacuum degassing section is maintained at -0.082 MPa. After pelleting, the pellets are dried in an oven at 85℃ for 3.0 h to obtain modified pellets.
[0050] Then, monofilament melt spinning extrusion is performed. The length-to-diameter ratio of the spinning screw is 30:1. The spinning temperature settings are: 210℃ in the melting zone, 230℃ in the extrusion zone, and 225℃ in the spinneret. The spinneret orifice diameter is 0.9mm, the water temperature in the quenching water tank is 55℃, and the traction linear speed is 18m / min. The filaments are then extruded into nascent fine filaments.
[0051] Finally, a three-stage gradient hot stretching and surface phase separation and setting process was carried out; the nascent filaments were stretched 5.0 times at the first-stage stretching temperature of 132℃ and 1.6 times at the second-stage stretching temperature of 162℃, with a total stretching ratio of 8.0 times; the third-stage heat setting temperature was 172℃, and the heat setting was carried out for 5 seconds while maintaining a 2% overfeed shrinkage rate, finally producing a high-strength wear-resistant fluorocarbon wire with a diameter of 0.28mm.
[0052] Comparative Example 1 This comparative example did not undergo aqueous suspension copolymerization modification of the vinylidene fluoride active precursor resin. 1000 kg of commercially available vinylidene fluoride pure resin powder with a weight-average molecular weight of 520,000 was used to directly replace the precursor powder prepared in Example 1. The material ratios and process conditions for subsequent melt reaction blending granulation, monofilament melt spinning extrusion, and three-stage gradient thermal stretching and surface phase separation and shaping were exactly the same as in Example 1.
[0053] Comparative Example 2 In this comparative example, no polyether diamine was added during the melt reaction blending and granulation process. The aqueous suspension copolymerization process was exactly the same as in Example 1. During the melt reaction blending and granulation process, polypropylene glycol bis(2-aminopropyl) ether D2000 was not added, and the remaining component ratios and subsequent spinning, extrusion, and three-stage gradient stretching and setting process conditions were exactly the same as in Example 1.
[0054] Comparative Example 3 In this comparative example, no phase transfer catalyst was added during the melt reaction blending and granulation process, and the aqueous suspension copolymerization process was exactly the same as in Example 1. During the melt reaction blending and granulation process, no benzyltriphenylphosphine chloride phase transfer catalyst was added, and the remaining component ratios and subsequent spinning, extrusion, and three-stage gradient stretching and shaping process conditions were exactly the same as in Example 1. The lack of a polar catalyst led to a significant reduction in the ammonolysis reaction efficiency and insufficient exfoliation of the montmorillonite layers. X-ray diffraction testing showed that the interlayer spacing of the modified montmorillonite increased by less than 8%.
[0055] like Figure 1 As shown, the (001) crystal plane diffraction peak of the MMT raw material is located at 2θ=3.60° (d001=2.45nm). In Comparative Example 3 without phase transfer catalyst, the diffraction peak shifts slightly to the left to 2θ=3.37° (d001=2.45nm). 001 =2.62 nm, with an expansion of only 6.9%), indicating that the filler is in a multi-layered aggregated state. Example 1 introduced a polar phase-transfer catalyst combined with in-situ ammonolysis, significantly reducing the interfacial free energy, and the diffraction peak shifted to the left to 2θ = 2.65° (d 001 =3.33nm, with an expansion of 35.9%) and peak broadening, confirming that MMT achieves efficient intercalation and local in-situ exfoliation, forming a uniformly dispersed two-dimensional reinforcement phase.
[0056] Comparative Example 4 The three-stage gradient hot stretching was not used. Other preparation methods and conditions were the same as in Example 1. In the subsequent stretching and shaping process, the second-stage micro-stretching and the third-stage heat shaping were cancelled. Instead, a single-stage stretching was performed at 125°C until the total stretching ratio was 8.1 times, and then the product was directly blown dry and wound.
[0057] Performance Testing – Analysis of Spacing Between Montmorillonite Stripping Layers X-ray diffraction (XRD) was used to characterize the crystal structure and interlayer spacing of the modified fluorocarbon pellets and montmorillonite raw materials prepared in Examples 1-2 and Comparative Examples 1-4. The testing conditions were: CuKα radiation source, wavelength λ = 0.15406 nm, tube voltage 40 kV, tube current 40 mA, scanning range 2θ = 1.5°–10°, scanning step size 0.02°, and scanning speed 1° / min. The 001 interplanar spacing d of the modified montmorillonite in the resin matrix was calculated according to the Bragg equation λ = 2dsinθ. 001The increase in the spacing between montmorillonite layers was calculated according to the following formula. Each group of samples was measured independently three times, and the average value of the results was taken. The test data are shown in Table 1.
[0058] ; Table 1 Results of montmorillonite peeling layer spacing in Examples 1-2 and Comparative Examples 1-4
[0059] The test results above show that the interlayer spacing of the modified montmorillonite in Examples 1-2 was significantly increased compared to the raw material. This confirms that during the twin-screw extrusion process, the high shear field in reaction zones two and three promotes the nucleophilic ammonolysis reaction between the polyether diamine and the side ester groups. The resulting flexible nodes, in synergy with the phase transfer catalyst, reduce the interfacial energy between the resin and the inorganic layered filler, promoting the intercalation of the fluorocarbon resin macromolecular chains and facilitating the in-situ exfoliation of the montmorillonite sheets. In contrast, Comparative Example 2, lacking polyether diamine, could not form ammonolysis flexible nodes, resulting in a lower interlayer spacing compared to the examples. Comparative Example 3, lacking a phase transfer catalyst, suffered from low ammonolysis efficiency, insufficient montmorillonite exfoliation, and a reduced proportion of increased interlayer spacing, demonstrating the positive role of polar catalysis and in-situ ammonolysis in driving the exfoliation of inorganic materials.
[0060] Performance Test 2: Tensile strength and elongation at break test, surface static and dynamic friction coefficient test, and abrasion resistance test. First, the tensile strength and elongation at break tests were performed on the fluorocarbon wires prepared in Examples 1-4 and Comparative Examples 1-4 using a special anti-slip winding monofilament clamp. The clamping distance was set to 250 mm, the tensile speed to 200 mm / min, the ambient temperature to 23 °C, and the relative humidity to 49%. Ten parallel tests were conducted on each sample, and the average value and standard deviation of the tensile strength (in MPa) and elongation at break (in %) were calculated.
[0061] Second, the static and dynamic friction coefficients were tested using an MXD-02 friction coefficient meter according to ISO 8295 standard. Multiple monofilaments of fluorocarbon wire were laid parallel and tightly fixed on the test platform, forming a wire test surface with dimensions no less than 50 mm × 50 mm on a flat substrate. The bottom surface of the slider was made of standard polished stainless steel, the slider mass was 200g, the test stroke was 70 mm, and the sliding speed was 100 mm / min. The system automatically recorded the initial maximum tension and the average tension during the sliding process, and calculated the static and dynamic friction coefficients.
[0062] Third, the abrasion resistance test was conducted according to ISO 9352 standard. The abrasion resistance level of the fluorocarbon wire was evaluated using a Taber 5135 rotary abrasion tester. An H-18 grinding wheel was used, with a single-sided load of 1000g. The wire was rotated for 5000 revolutions at 23℃. The mass loss (in milligrams) before and after abrasion was recorded. The abrasion resistance level was evaluated based on the mass loss and wire diameter change, with level 1 being the highest and level 5 being the lowest. The test results are summarized in Table 2.
[0063] Table 2. Overall performance test results of Examples 1-4 and Comparative Examples 1-4
[0064] As shown in Table 2, the high-strength wear-resistant fluorocarbon wires prepared in Examples 1-4 of this invention exhibit good mechanical properties, self-lubricating characteristics, and good wear resistance. Through step (1) aqueous suspension copolymerization, active ester side groups are imparted to the precursor; in step (2) melt blending, polyether diamine undergoes in-situ ammonolysis crosslinking to construct a flexible network, combined with exfoliated montmorillonite and nano-hexagonal boron nitride, thereby improving the mechanical strength and toughness of the matrix and its surface wear resistance; simultaneously, step (4) three-level gradient thermal stretching and surface phase separation shaping result in highly oriented macromolecular chains and the formation of a self-lubricating phase on the surface. Figure 2 and Figure 3 As shown, Example 1 exhibits excellent balance between stiffness and toughness, with improved tensile strength and elongation at break. This is attributed to the dispersion of stress in the crosslinked network constructed by the exfoliated MMT and h-BN, as well as the flexible nodes. Comparative Example 1, lacking a copolymer precursor containing active ester side groups, cannot undergo ammonolysis, leading to filler agglomeration, decreased tensile strength, and insufficient load-bearing capacity. Comparative Example 4, without secondary micro-stretching and heat setting, fails to achieve highly ordered orientation and high crystallinity, exhibiting early brittle fracture. Example 1 shows a reduced static friction peak and stable steady-state dynamic friction coefficient without stick-slip oscillations, stemming from the directional arrangement of the exfoliated filler at the interface, forming a dense self-lubricating network. Comparative Example 1 shows an increased static friction peak and a higher dynamic friction coefficient with severe oscillations, due to the mechanical interlocking and interfacial tearing caused by the unexfoliated particles. Comparative Example 4 shows an increased dynamic friction coefficient with irregular amplitude fluctuations, caused by the lack of heat setting, resulting in decreased surface hardness and wear-resistant density, leading to micro-area peeling.
[0065] Comparative Example 1, without copolymerization modification using an active precursor, lacked chemical crosslinking nodes and nano-exfoliation reinforcement in its matrix, resulting in decreased tensile strength, a significantly increased coefficient of friction, and a drop in wear resistance. Comparative Examples 2 and 3, lacking polyether diamine or phase transfer catalysts, could not undergo in-situ ammonolysis and sufficient exfoliation of inorganic materials, leading to stress concentration within the composite material and a significant decrease in tensile strength and wear resistance. Comparative Example 4, without secondary micro-stretching and tertiary heat setting, suffered from poor tensile strength and decreased elongation at break due to insufficient high-order orientation and stress relaxation of the macromolecular chains, resulting in brittle fracture. These findings demonstrate the irreplaceable role of the three-stage gradient ultra-stretching and surface phase separation process in improving the overall performance of fluorocarbon wires.
Claims
1. A method for preparing a high-strength, wear-resistant fluorocarbon wire, characterized in that, By weight, it includes the following raw materials: 1000 parts of vinylidene fluoride copolymer precursor powder, 5.0-10.0 parts of polyether diamine, 0.03-0.08 parts of phase transfer catalyst, 1.0-8.0 parts of lubricating and friction-reducing nanoparticles, and 1.0-10.0 parts of inorganic layered filler; The vinylidene fluoride copolymer precursor powder is copolymerized from vinylidene fluoride monomer and fluorinated acrylate monomer; the lubricating and friction-reducing nanoparticles are selected from one of hexagonal boron nitride nanosheets, molybdenum disulfide nanosheets, tungsten disulfide nanosheets, and graphene nanosheets; the inorganic layered filler is selected from one of octadecyltrimethylammonium chloride modified montmorillonite, quaternary ammonium salt modified hydrotalcite, and organic modified kaolinite. The method for preparing wear-resistant fluorocarbon wire The process includes the following steps: adding deionized water and a suspending agent to the reactor to remove oxygen from the system, then adding fluorinated acrylate monomers, vinylidene fluoride monomers, and chain transfer agents, heating to 35-55℃ and adding an initiator for aqueous suspension copolymerization, supplementing vinylidene fluoride monomers during polymerization to maintain the reactor pressure at 3.0-4.0 MPa, reacting for 3.5-6.0 h, and then separating, washing, and drying to obtain the vinylidene fluoride copolymer precursor powder; The vinylidene fluoride copolymer precursor powder, the polyether diamine, the phase transfer catalyst, the lubricating and friction-reducing nanoparticles, and the inorganic layered filler were dry-mixed and fed into a twin-screw extruder with an aspect ratio of 36:1-48:1 for melt blending extrusion, water-cooled granulation, and drying to obtain modified fluorocarbon pellets with a moisture content of less than 200 ppm. The modified fluorocarbon pellets are fed into a single-screw spinning machine, extruded into nascent filaments through a spinneret, and then quenched and cured in a water bath at 30-65°C with a traction speed of 10-22 m / min. The nascent filaments are subjected to a first-stage stretch of 3.5-5.2 times at 110-140℃ and a second-stage stretch of 1.2-2.2 times at 140-170℃, resulting in a cumulative total stretch of 6.0-9.5 times. Then, they are subjected to a third-stage heat setting at 155-180℃ with an overfeed shrinkage rate of 1%-6% for 4-10 seconds to obtain the wear-resistant fluorocarbon wire with a diameter of 0.15-0.40mm.
2. The method for preparing high-strength wear-resistant fluorocarbon wire according to claim 1, characterized in that, The polyether diamine is selected from one of polypropylene glycol bis(2-aminopropyl) ether D2000, polypropylene glycol bis(2-aminopropyl) ether D400, and ED2003, a polymer of methyl ethylene oxide and ethylene oxide and bis(2-aminopropyl) ether; the phase transfer catalyst is selected from one of benzyltriphenylphosphine chloride, tetrabutylphosphine bromide, tetrabutylammonium bromide, tetrabutylammonium hydrogen sulfate, and trioctylmethylammonium chloride.
3. The method for preparing high-strength wear-resistant fluorocarbon wire according to claim 1, characterized in that, The preparation method of the octadecyltrimethylammonium chloride modified montmorillonite is as follows: sodium montmorillonite is heated to 70°C in deionized water for high-shear dispersion, swelling and exfoliation, and then an ethanol aqueous solution of octadecyltrimethylammonium chloride is pumped in and reacted at 82°C for 3.5 hours. The mixture is then obtained by pressure filtration, washing, drying and air jet milling.
4. The method for preparing high-strength wear-resistant fluorocarbon wire according to claim 1, characterized in that, The preparation method of the quaternary ammonium salt modified hydrotalcite is as follows: a salt solution of magnesium nitrate and aluminum nitrate, and an alkaline solution of sodium hydroxide, sodium carbonate and hexadecyltrimethylammonium bromide are simultaneously pumped into a co-precipitation vessel, the pH is adjusted and hydrothermally crystallized at 105°C for 10 hours, and then obtained by pulping and centrifugal spray drying.
5. The method for preparing high-strength wear-resistant fluorocarbon wire according to claim 1, characterized in that, The preparation method of the organic modified kaolin is as follows: calcined kaolin is added to a mixture of dimethyl sulfoxide and deionized water, intercalated at 65°C for 36 hours, filtered by pressure, and then dispersed by adding an aqueous ethanol solution. The pH is adjusted to 4.8, and an ethanol solution of silane coupling agent KH-550 and octadecylamine is added. The mixture is refluxed at 78°C for 5 hours, and then pulverized under vacuum and a closed nitrogen protective gas flow to obtain a finished product with a mesh size of 325 or higher.
Citation Information
Patent Citations
Yarn incorporating fluoropolymer staple fiber
CN111065769A
Polytetrafluoroethylene porous fiber and manufacturing and modifying process thereof
US20240318358A1